Isolation of Vibrio harveyi acyl carrier protein and the fabG, acpP, and fabF genes involved in fatty acid biosynthesis. - Shen, Z (1996)
We report the isolation of Vibrio harveyi acyl carrier protein (ACP) and cloning of a 3,973-bp region containing the fabG (encoding 3-ketoacyl-ACP reductase, 25.5 kDa), acpP (encoding ACP, 8.7 kDa), fabF (encoding 3-ketoacyl-ACP synthase II, 43.1 kDa), and pabC (encoding aminodeoxychorismate lyase, 29.9 kDa) genes. Predicted amino acid sequences were, respectively, 78, 86, 76, and 35% identical to those of the corresponding Escherichia coli proteins. Five of the 11 sequence differences between V. harveyi and E. coli ACP were nonconservative amino acid differences concentrated in a loop region between helices I and II.